2018
DOI: 10.1158/1538-7445.am2018-ct180
|View full text |Cite
|
Sign up to set email alerts
|

Abstract CT180: Preliminary phase 1 profile of BMS-986179, an anti-CD73 antibody, in combination with nivolumab in patients with advanced solid tumors

Abstract: Background: CD73 is an ectonucleotidase that converts adenosine monophosphate to adenosine, a potent immunosuppressive soluble mediator that inhibits the cytotoxic function of CD8+ T cells and natural killer cells while promoting proliferation of immunosuppressive cells. BMS-986179 is a high-affinity antibody that inhibits CD73 enzymatic activity and downregulates its expression on tumor cells. Blockade of CD73 enhanced the antitumor activity of anti-PD-1 in preclinical models (Barnhart BC, et al. Cancer Res. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 0 publications
4
35
0
Order By: Relevance
“…Accordingly, several clinical trials inhibiting CD73 (e.g., antibodies against CD73 or small molecule inhibitors) in combination with ICI therapy, A2AR antagonism, targeted therapy, and/or chemotherapy are underway ( Table 3). Preliminary safety profiles report BMS-986179, an anti-CD73 humanized monocolonal antibody, and its combination with nivolumab (anti-PD-1 therapy) to be well-tolerated in patients (NCT02754141) (251). Recent studies in renal cell cancer (RCC) reported the feasibility and safety of A2AR antagonist, ciforadenant (124).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, several clinical trials inhibiting CD73 (e.g., antibodies against CD73 or small molecule inhibitors) in combination with ICI therapy, A2AR antagonism, targeted therapy, and/or chemotherapy are underway ( Table 3). Preliminary safety profiles report BMS-986179, an anti-CD73 humanized monocolonal antibody, and its combination with nivolumab (anti-PD-1 therapy) to be well-tolerated in patients (NCT02754141) (251). Recent studies in renal cell cancer (RCC) reported the feasibility and safety of A2AR antagonist, ciforadenant (124).…”
Section: Discussionmentioning
confidence: 99%
“…Future studies in GI cancers that focus on determining if adenosine-mediated resistance to immunotherapy therapy exists at diagnosis or evolves with therapy will also be of significant benefit. Encouraging early results for BMS-986179 combined with nivolumab report clinical benefit (partial response) in one or more patients with pancreatic and prostate cancer (NCT02754141) (251). Both are poorly immunogenic tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, MEDI9447 decreased CD73 expression in five out of nine tumors, which correlated with increased cytotoxic T cell infiltration (83). The αCD73 mAb BMS986179 as a monotherapy and in combination with the PD-1 inhibitor nivolumab also induced partial responses or stable disease in 17 of 59 patients with various malignancies (84).…”
Section: Cd39/cd73mentioning
confidence: 93%
“…Practical approaches to target the adenosinergic pathway and adenosine A 2A receptor signaling CD39 inhibits the immune system by degrading ATP into AMP, which is then further degraded into adenosine by CD73. In the last decade, CD73, CD39, and A 2A R receptors' potential as immunotherapy targets for cancer and microbial infections have rapidly increased [17][18][19][20][21][22]. Humanized monoclonal anti-CD39, such as IPH5201 (Innate Pharma), have been developed [23].…”
Section: Ectonucleotidases and Adenosine Receptor Activity Promote Immentioning
confidence: 99%